Bioactive injectable hydrogels for on demand molecule/cell delivery and for tissue regeneration in the central nervous system. (1st March 2022) - Grimaudo, M.A.; Krishnakumar, G.S.; Giusto, E.; Furlani, F.; Bassi, G.; Rossi, A.; Molinari, F.; Lista, F.; Montesi, M.; Panseri, S
Abstract: Currently there are no potential curative therapies that can improve the central nervous system (CNS) regeneration after traumatic injuries or diseases. Indeed, the regeneration of CNS is greatly impaired by limited drug penetration across the blood brain barrier (BBB), poor drug targeting, deficient progenitor neural cells and limited proliferation of mature neural cells. To overcome these limitations, bioengineered injectable hydrogels in combination with drug and cell therapy have been proposed to mimic the complexity of the CNS microenvironment and architecture. Additionally, to enhance relevant CNS regeneration, proper biophysical and biochemical cues are needed. Recently, great efforts have been devoted to tailor stimuli-responsive hydrogels as novel carrier systems which are able to guide neural tissue regeneration. This review provides an extensive overview on the most promising injectable hydrogels for neural tissue engineering. A special emphasis is made to highlight the ability of these hydrogels to deliver bioactive compounds/cells upon the exposure to internal and external stimuli. Bioactive injectable hydrogels have a broad application in central nervous system's (CNS) regeneration. This review gives an overview of the latest pioneering approaches in CNS recovery using stimuli-responsive hydrogels for several neurodegenerative disorders. Statement of significance: This review summarizes the latest innovations on bioactive injectable hydrogels, focusing on tailoring internal/external stimuli-responsive hydrogels for the new injectable systems design, able to guide neural tissue response. The purpose is to highlight the advantages and the limitations of thermo-responsive, photo responsive, magnetic responsive, electric responsive, ultrasound responsive and enzymes-triggered injectable hydrogels in developing customizable neurotherapies. We believe that this comprehensive review will help in identifying the strengths and gaps in the existing literature and to further support the use of injectable hydrogels in stimulating CNS regeneration. Graphical abstract: Image, graphical abstract